On the transverse magnetization of the anisotropic superconductor 2H-NbSe₂ - Sirenko, V.A.; Makedonska, N.I.; Shabakayeva, Yu. A. (Физика низких температур, 2002)
Torque measurements were performed on a high-quality single crystal of the uniaxial superconductor 2H-NbSe₂ in a tilted magnetic field 0–200 kG, in the temperature range 1.5–4.2 K. The transverse component of the absolute magnetization was derived in a magnetic field directed at an angle of 77° to the axis of anisotropy, and its field dependence was analyzed in a reversible domain of the mixed state. The penetration depth and anisotropy characteristics were obtained for the sample under study.